Case Story 8: Multi-stakeholder Prioritization Approach for Climate-Smart Agriculture Planning and Investment in Vietnam. - Corner-Dolloff, Caitlin; Nowak, Andreea C.; Lizarazo, Miguel; Parker, Louis; Van Trinh, Mai; Nghia, Tran Dai (SEARCA, 2016)
This case story outlines the results of a national research initiative that utilized the Climate-Smart Agriculture Prioritization Framework (CSA-PF) to inventory, assess, and prioritize CSA options with stakeholders for various subnational regions. The CSA‑PF is a four-phase process, which was implemented in Vietnam under the direction of the Ministry of Agriculture and Rural Development. In the first phase, a compendium of CSA practices was created, characterizing over 807 farms using 111 categories of practices across Vietnam. The practices were then analyzed twice using a set of CSA indicators, at first rapidly by experts to select 13 promising practices (11 crop, 2 livestock), and the second time through detailed surveys to better understand the trade‑offs (Phase 2). Eight practices were selected for detailed cost-benefit analyses, which were carried out in Phase 3 by the Institute of Policy and Strategy for Agriculture and Rural Development. Economic evaluations were conducted in specific productions systems in regions of high importance to the agriculture sector and vulnerable to climate change (Red River Delta, Mekong River Delta, and South Central Coast). It was found that rice-shrimp rotations, integrated crop management in rice, and mixing rice crops and mushroom growing were some of the most profitable and low-risk options. The fourth phase, which is ongoing, will bring stakeholders together to establish investment portfolios of CSA priorities and action plans. All previous analyses will be utilized to prioritize and discuss strategies for minimizing trade-offs, increasing synergies between practices, avoiding or overcoming barriers to adoption, and linking with end user priorities.